Beekeeping Activities II: The Evaluaton of Beekeeping Activities in terms of Beekeeper Preferences, Production Quality and Bee Diseases in Malatya Province - Seker, Ibrahim; Koseman, Abdurrahman; Karlidag, Semiramis; Aygen, Selami (Univ Namik Kemal, 2017)
This research was conducted to determine the conditions of beekeeping in Malatya in caring, feeding, breeding and production activities. Face to face interviews with 149 beekeepers were applied by using the random sampling method in selected registered beekeepers to Beekeeping Registration System (BRS). In this study, it is found that 83.7 % of beekeepers use Standard Langstroth Hives, 15.4 % produce bee productions except honey, 57.0 % renovate queen bee once in two years and 83.9 % buy queen bee but not breed it. In this study, it is determined that breeders use 80.5 % Caucasian crossbred bee, and 79.2 % breeders do not use simple selection. In the current study, it is calculated that the ratio of 97.3 % sucrose is used for syrup making, the most common bee disease is varroosis (47.8 %), 69.1 % beekeeping do not have records, 90.5 % of keepers are strollers and 35.2 % do not consider themselves having sufficient beekeeping knowledge and practice. To have a better beekeeping in Malatya, it is necessary to use efficient and local adapted races, give importance to breeding queen bees, keep business records, encourage the production of bee products except honey, fight for the diseases densely and conduct courses, trainings and information activities for beekeepers extensively.
Arıcılık faaliyetleri II: Malatya İlinde arıcılık faaliyetlerinin yetiştirici tercihleri, üretim nitelikleri ve arı hastalıkları kapsamında değerlendirilmesi
Keywords: Beekeeping; Queen Bee; Honey bee (Apis mallifera L.); Varroosis